Tuft Cells Increase Following Ovine Intestinal Parasite Infections and Define Evolutionarily Conserved and Divergent Responses - Hildersley, Katie A.; McNeilly, Tom N.; Gillan, Victoria; Otto, Thomas D.; Löser, Stephan; Gerbe, François; Jay, Philippe; Maizels, Rick M.; Devaney, Eileen; Britton, Collette (Frontiers in Immunology, 2021)
Helminth parasite infections of humans and livestock are a global health and economic problem. Resistance of helminths to current drug treatment is an increasing problem and alternative control approaches, including vaccines, are needed. Effective vaccine design requires knowledge of host immune mechanisms and how these are stimulated. Mouse models of helminth infection indicate that tuft cells, an unusual type of epithelial cell, may ‘sense’ infection in the small intestine and trigger a type 2 immune response. Currently nothing is known of tuft cells in immunity in other host species and in other compartments of the gastrointestinal (GI) tract. Here we address this gap and use immunohistochemistry and single cell RNA-sequencing to detail the presence and gene expression profile of tuft cells in sheep following nematode infections. We identify and characterise tuft cells in the ovine abomasum (true stomach of ruminants) and show that they increase significantly in number following infection with the globally important nematodes Teladorsagia circumcincta and Haemonchus contortus. Ovine abomasal tuft cells show enriched expression of tuft cell markers POU2F3, GFI1B, TRPM5 and genes involved in signalling and inflammatory pathways. However succinate receptor SUCNR1 and free fatty acid receptor FFAR3, proposed as ‘sensing’ receptors in murine tuft cells, are not expressed, and instead ovine tuft cells are enriched for taste receptor TAS2R16 and mechanosensory receptor ADGRG6. We also identify tuft cell sub-clusters at potentially different stages of maturation, suggesting a dynamic process not apparent from mouse models of infection. Our findings reveal a tuft cell response to economically important parasite infections and show that while tuft cell effector functions have been retained during mammalian evolution, receptor specificity has diverged. Our data advance knowledge of host-parasite interactions in the GI mucosa and identify receptors that may potentiate type 2 immunity for optimized control of parasitic nematodes.